Influence of preheating source on mechanical properties and welding residual stress characteristics in ultra thin ferritic stainless steel hybrid friction stir welded joints - Kim, Kyoung-Hak; Bang, Han-Sur; Ro, Chan-Seung; Bang, Hee-Seon (International Journal of Precision Engineering and Manufacturing-Green Technology, 4(4), 2017)
The joining of ultra thin ferritic stainless steel (STS) with thickness of 0.5 mm has been carried out by Hybrid Friction Stir Welding (HFSW) without pin method using additional Gas Tungsten Arc Welding (GTAW) as preheating source. The influence of preheating source on mechanical properties and welding residual stress characteristics has been investigated through mechanical test and numerical analysis. The ultimate tensile strength of HFSWelded joints is approximately 103% of base metal tensile strength which is higher than that of FSWelded joints. From the result of numerical analysis for thermal elastic-plastic analysis, it is founded that the magnitude of residual stress component (σx) of welding direction is in following order: HFSWelded joints (470 MPa) >FSWelded joints (400 MPa). For the stress component (σy) of perpendicular direction to welding line, there is no great difference for maximum tensile residual stress of FSWelded joints (180MPa) and HFSWelded joints (200 MPa). On the other hand, the area of residual stress distributions in HFSW is smaller than FSW method. The overall results obtained in mechanical test and numerical analysis confirmed that HFSW is a distinct possibility to join ultra thin STS.